Fibroblast Growth Factor 21 as a Marker of Prediabetes in Patients with Non-alcoholic Fatty Liver Disease - Karamfilova, Vera; Assyov, Yavor; Nedeva, Iveta; Gateva, Antoaneta; Ivanova, Irena; Cherkezov, Nikolay; Mateva, Ludmila; Kamenov, Zdravko (Turkish Journal of Gastroenterology, 2022)
Background: Fibroblast growth factor 21 is a peptide primarily secreted by the liver in response to peroxisome proliferator-activatedreceptor-α activation which plays an important role in regulating carbohydrate and lipid metabolism. This study investigated the association between fibroblast growth factor 21 and prediabetes in obese patients with non-alcoholic fatty liver disease in adult population.Methods: A total of 85 obese non-alcoholic fatty liver disease patients without (n = 49) and with prediabetes (n = 36) were included.Serum fibroblast growth factor 21 levels were determined by enzyme-linked immunosorbent assay.Results: Higher fibroblast growth factor 21 serum levels were observed in patients with prediabetes, metabolic syndrome, dyslipidemia, and insulin resistance. There were significant correlations between fibroblast growth factor 21 and waist-to-stature ratio, visceral adiposity index, triglycerides, very low-density lipoproteins, alanine aminotransferase (ALT), gamma-glutamyl transferase (GGT),Quantitative Insulin Sensitivity Check Index, and Stumvoll index of insulin sensitivity. Fibroblast growth factor 21 level ≥320 pg/mL wasassociated with a 4.2-fold higher risk of prediabetes and ≥270 pg/mL for metabolic syndrome approximately 4 times.Conclusion: Fibroblast growth factor 21 is associated with increased risk for prediabetes, metabolic syndrome, and insulin resistance inobese patients with non-alcoholic fatty liver disease.